The mitochondrial genomes of five frog species of the Neotropical genus Ischnocnema (Anura: Brachycephaloidea: Brachycephalidae) - Taucce, Pedro P. G. [UNESP] (2018)
We report the mitogenomes for five species of the Ischnocnema guentheri series, being the first described for this genus of brachycephalid frogs. We assembled mitogenomes from anchored hybrid enrichment data and recovered the 13 protein-coding genes, 22 tRNA genes, and two rRNA genes for all species. The general structure agrees with most previously sequenced neobatrachians, with two exceptions: the origin of replication of L-strand (OL) was found between tRNA-A and tRNA-N, and the position of tRNA-L and tRNA-T, which are dispersed in the control region. We provide a phylogenetic tree with outgroups, which is consistent with previous phylogenetic hypotheses.